THE DEVELOPMENT OF RESPIRATORY SYSTEM TEACHING MATERIAL SUPPLEMENT AS A CARING FORM OF THE DANGERS OF E-CIGARETTES FOR HEALTH - Nuha, Ulin; Lisdiana, Lisdiana (Journal of Biology Education, 2019)
Based on KD (Basic Competence) 3.8 and 4.8 of class XI curriculum 2013 in respiration system material, in learning must be started from relevant facts often faced by students, one of which is in the subject of respiratory system disorders. Along with the development of age, respiratory system disorders caused by exposure to cigarettes are a problem that often occurs in adolescents. So, it is necessary to supplement teaching materials that support the main teaching materials to achieve these learning goals. The purpose of this study is to analyze the feasibility and effectiveness of supplementary respiratory system teaching materials developed. The research uses the Research and Development (R&D) method based on 10 steps of R & D research in Sugiyono (2015). The test and indicators for determining the feasibility and effectiveness of supplementary teaching materials are (1) feasibility tests include the study test and readability test each ? 51%, (2) test the effectiveness in improving learning outcomes with classical completeness test ? 70% of students who achieved a value of ? 70, medium to high N-gain test, and sensitivity index items ? 0.30, (3) effectiveness test in growing students' caring attitudes students with the percentage scale score of caring attitude ? 51%. The results show that the feasibility test is obtained by a 95% review test and 93% readability test, the effectiveness test for improving learning outcomes showed 87.5% of classical completeness results, N-gain score 0.7 (high), item sensitivity index questions 0.4 (sensitive), the effectiveness test in growing caring attitude shows overall on the caring criteria (there are 2 students or 6.25%) and very caring (there are 30 students or 93.75%). The conclusions in this study are respiration system supplementary material as supplementary teaching material is appropriate and effective in improving learning outcomes and also effectively fostering caring attitudes of students towards the dangers of e-cigarettes for health.